Pemanfaatan SIG Untuk Model Pemetaan Zona Potensial Penangkapan Ikan di Perairan Lampung - Rachmadi, Rachmadi; Triloka, Joko; Yusuf Irianto, Suhendro; Sriyanto, Sriyanto (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
The waters in the Lampung region have significant potential as fishing areas. Fisheries potential in the Lampung region is supported by various factors, including a climate that supports plankton growth and a fertile ecosystem, as well as a variety of habitats that are suitable for various types of fish. In addition, traditional coastal activities such as fishing, boat fishing, and fish farming in ponds are also an important part of the local economy. However, so far fisheries management is still not optimal, it is important to manage fisheries potential optimally and sustainably. This research aims to present a geographic information system modeling regarding weather changes in the Lampung region and its surroundings in order to optimize fishing activities in Lampung waters. Data analysis uses Aqua MODIS data extraction as well as wind data gridding and description. The research results show that the waters in Lampung Province have significant potential regarding the presence of fish based on SST distribution. Keywords— Geographic information system, weather data, lampung waters, aqua modis